Gestão de obras públicas: análise dos aditivos financeiros e temporais nos contratos de obras da Universidade Federal do Espírito Santo no período de 2009 a 2015 - Casotte, Anderson Geraldo Zanotelli (2016)
We propose in this research to analyze the intensity and the reasons for the realization of financial and temporal additives in the construction and reform works of the Universidade Federal do Espírito Santo from 2009 to 2015. The essential justification for proposing these projects by the Public Administration is found in benefits these actions will bring to the population. Starting from the premise that there is a need for improvement in the provision of public services to society, is evident the imperative of increasing efficiency and effectiveness of reforms and structural works. In this way, public managers are expected to make the most of their efforts to achieve the desired goal, using the most economical and viable means, maximizing results and minimizing costs. The methodology used in this research was bibliographic documental, qualitative and quantitative. The results indicated the existence of dysfunctions, since 62% of the total reform and construction work required financial additives, while 65% of the projects were subject to temporary additions. The increase in costs of these works was, on average, 20% higher than the value initially contracted. The deadline for the delivery of the works, in turn, delayed more than double the time provided in the contractual instruments. Our research also shows that the quantity of additives signed by Ufes grew during the interstice chosen for analysis, suggesting that the experiments of the additives did not serve as learning for the administrative teams of the University responsible for drafting contracts. We found that the main reasons for the elaboration of the contractual additives were based on the need for technical adaptation of the projects of reform and/or structural work, followed by the need to include services not foreseen in the original project and requested by the contractor. We believe that, at the end of the research, we contributed to the discussion of the contractual additives with the proposition of possible solutions in order to minimize the localized problems.